2020
DOI: 10.3390/jcm9092798
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Conditioned Media on the Re-Differentiation Capacity of Human Chondrocytes in 3D Spheroid Cultures

Abstract: A major challenge of cell-based therapy for cartilage lesions is the preservation of the chondrogenic phenotype during ex vivo cell cultivation. In this in vitro study, the chondro-inductive capacity of two different hyaline cartilage-conditioned cell culture media on human chondrocytes in 3D spheroids was determined. Media were conditioned by incubation of 200 mg/mL vital or devitalized cartilage matrix in growth media over 35 days. The media were analyzed for the content of soluble procollagen type (Col) II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…It is conceivable that these changes caused by HHP enable mediators to diffuse into the cell culture medium where they influence cell differentiation. Such an effect of HHP was already hypothesized by Klinder et al 32 Although the release of various matrix proteins into the surrounding medium over a prolonged period of time could be detected, no differences between control and HHP treatment were observed 32 . However, Klinder et al 32 focused on cartilage, which is characterized by a compact matrix 33 .…”
Section: Discussionmentioning
confidence: 81%
“…It is conceivable that these changes caused by HHP enable mediators to diffuse into the cell culture medium where they influence cell differentiation. Such an effect of HHP was already hypothesized by Klinder et al 32 Although the release of various matrix proteins into the surrounding medium over a prolonged period of time could be detected, no differences between control and HHP treatment were observed 32 . However, Klinder et al 32 focused on cartilage, which is characterized by a compact matrix 33 .…”
Section: Discussionmentioning
confidence: 81%
“…Culturing chondrocytes in a 3D environment has been widely proposed as a promising approach as it can mimic native articular signaling by re-establishing a specific phenotype and cellular functions of the cartilage compared with other previously reported methods not related to the spheroid generation [ 29 , 30 , 31 ]. Significantly, the 3D model triggers a tissue-specific phenotype due to cell–cell and cell–ECM interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In this translational study, we chose to use human dermal substrate as vector to transduce human AT-MSC-derived chondrocytes since the human skin/dermis remains one of the most efficient sites of type II collagen matrix, significant to accommodate chondrocytes in generating very close biosimilar cartilage-like tissue [ 19 , 20 ]. After a long-term follow-up (11 years) on 61 patients after autologous chondrocyte transplantation graft procedures, it was observed that all of the specimens stained positive for COMP and aggrecan.…”
Section: Discussionmentioning
confidence: 99%